Mindfulness and Self-Rediscovery: Strategies for Reclaiming Happiness in a Materially Rich but Emotionally Challenged Society - Awais Ur Rahman; Awais Yaseen; Arfa Akram; Hafsa Khanam; Muhammad Asif; Rubia Batool (Research Journal of Psychology, 2025)
Psychologically wealthy but emotionally deprived societies were the focus of our study with mindfulness and self-discovery regarding happiness. Moreover, to the purpose of the use of these practices for emotional well-being, interviews based on a qualitative approach were carried out with 20 participants. The quantitative analysis revealed how mindfulness, that included meditation and breath awareness supported stress, emotion regulation and focused attention in the present. Self-rediscovery which involved orientation to one’s fundamental self, changed participants’ goal from the external or tangible to internal or lofty, enhancing their overall Levels of life satisfaction. The findings will also underscore the significance of mindfulness and self-search for the upkeep of the emotional health of individuals in today’s’ conspicuous world of consumption. They bring useful tips for improving the state of happiness and mental health into focus.